The Medieval and Early Modern Hospital A Physical and Symbolic Space - Conejo da Pena, Antoni; Bridgewater Mateu, Pol (IRCVM-Medieval Cultures, 2023)
This volume explores the physical dimension of hospitals as both tangible buildings and symbolic vehicles, examining their impact on urban and rural landscapes. It serves as a testament to the current vitality of hospital studies in the Iberian Peninsula and territories once part of the Crown of Aragon. Contributions from diverse regions, including Northern and Central Italy and the Iberian Muslim world, enrich the discourse and showcase collaborative scholarly connections. The book is divided into four sections: an introduction to key themes, a collection of articles on hospital heritage and urban landscapes, an exploration of the relationship between hospitals and their surroundings, and a final section on medicine and epidemics. It encompasses the work of both established and emerging scholars, while also representing the professional and personal bonds fostered among researchers from different universities and centers.